Evaluation of health services: A directive for public health professionals - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava; Jegadeesh Ramasamy (Turkish Society of Public Health Specialists, 2015)
This letter provides information for the public health professionals and program managers to improve the reach of public health welfare strategies by ensuring effective evaluation of the existing services.